Cyfrowa (nie)moc dzieci przedszkolnych = The digital (dis)empowerment of preschool children - Walas, Barbara (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article is an attempt to show how preschool children use new technologies. The way in which they are prepared by their parents to receive information acquired by exploring the Internet is undeniably important for their development and learning. As regards children, media education is an extremely important issue. The knowledge and skills of their parents are a significant element of this education. An important part of the article is to present a part of research focused on the media reality of preschool children.
Keywords: new technologies; media; media education; media reality; preschool children; nowe technologie; edukacja medialna; rzeczywistość medialna; dziecko przedszkolne